Digital Metaphysics: The Cybernetic Idealism of Warren McCulloch. - Weatherby, Leif (Hedgehog Review)
The article focuses on cybernetic idealism of neurophysiologist Warren McCulloch in the digital metaphysics. It mentions experimental epistemology with metaphysician and philosophy of Immanuel Kant and era of Big Data and machine learning. It also mentions digital philosophy associated with Stephen Wolfram even maintains that matter itself is digital.